1984
DOI: 10.1136/ard.43.4.613
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological study of HLA and GM in rheumatoid arthritis and related symptoms in an open Dutch population.

Abstract: SUMMARY This report deals with the question of whether or not the established association of HLA-DR4 with rheumatoid arthritis (RA) can also be detected in cases of RA as diagnosed in a population survey. For this purpose 6584 persons older than 19 years living in a single community in The Netherlands were investigated for the presence of rheumatoid arthritis and related abnormalities. After five years 83 patients with RA, 30 with only erosive abnormalities on radiological examination (Rad), and 48 with only r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0
1

Year Published

1990
1990
2000
2000

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(18 citation statements)
references
References 17 publications
0
17
0
1
Order By: Relevance
“…However, with followup it was clear that patients who studies (10)(11)(12)23,24). Two possible explanations for this finding are that the action of the locus occurs after the initiation of RA or that patients with mild or self-limiting RA have an entirely separate disease that is not associated with the MHC.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…However, with followup it was clear that patients who studies (10)(11)(12)23,24). Two possible explanations for this finding are that the action of the locus occurs after the initiation of RA or that patients with mild or self-limiting RA have an entirely separate disease that is not associated with the MHC.…”
Section: Discussionmentioning
confidence: 94%
“…These data were derived from patients with chronic disease, although it had been assumed that this was a consequence of a major histocompatibility complex (MHC) effect on predisposition or susceptibility to disease. The observation that the strongest association between MHC and RA is with the most severe forms of disease (10)(11)(12) has led to speculation concerning the timing of the effect of the MHC. In a small selected group of patients, we recently showed that the genetic factors were predictive of progressive destructive disease (13).…”
mentioning
confidence: 99%
“…This distinction was initially suggested by a cross-sectional population based study of prevalent RA cases in the Netherlands, which found no association between HIA-DR4 and RA, but did find an association with radiological erosions. 6 Similarly, a recent study of incident cases of RA seen in general practice in Norfolk (the Norfolk Arthritis Register)7 found only a weak association with HLA-DR4. In contrast, most hospital clinic series of RA patients demonstrate a strong association with HLA-DR48 or the shared epitope, and this is more pronounced in patients with one of the most severe variants of RA, Felty's syndrome.…”
Section: Introductionmentioning
confidence: 96%
“…When there is a known genetic disease susceptibility, incorporation of genetic information in the investigation is important since without these data, the observable effect of an environmental factor could be diluted (17). An association between the HLA-DR4 antigen and RA has been well established (18)(19)(20); however, the question of whether DR4 is a marker for a susceptibility gene for severe RA (21) or a marker for a disease-modifying gene (22) has not been answered (23,24). Even if DR4 is only a marker for a disease-modifying gene, it would be of interest to know whether the protective effect of oral contraceptives is more specific for DR4-positive RA.…”
mentioning
confidence: 99%